People's participation in a relocation process a case study of the Balete Relocation Project undertaken by the Philippine Ports Authority in Batangas City, Philippines - Ahmad, Ijaz (1998)
The relocation process of urban poor families involving people's participation adopted by most government agencies in the Philippines has undergone several refinements over the years.Despite meticulous preparations at the start however,it has been noted that many of theses relocations have been marred by violence often resulting in physical injuries and even death in some instances.The present study once again looks at the relocation process, specifically, people's participation, to determine where in the relocation process do things actually go wrong.The relocation undertaken by the Philippine Ports Authority (PPA) in Sta. Clara in Batangas City between 1986 and 1994 has been selected as a case study. The relocation process is viewed by stages namely : Persuasion and Negotiation, Decision-Making, Implementation, and Resettlement and Adjustment. The roles of beneficiaries, government and non-government organizations (NGOs) in each stage are likewise evaluated.The main thesis of this study is that beneficiary participation is essential in any relocation effort. In all stages, it has been observed that because of insufficient participation, people are always wary of the sincerity of government. The entire process is seen as a testing ground whereby people try to find out for themselves how determined government is in fulfilling its promises.The role of POs/NGOs?ROs, especially in serving as a link between the beneficiaries and the government is also critical in the relocation process.It is hoped that findings derived from this case may be used to further refine the relocation process.